2017
DOI: 10.1097/id.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Localization of Frontal Bone Defects on Primary Stability Values of 2 Different Implant Designs

Abstract: Within the limitations of this study, it may be concluded that coronal defects may influence primary stability negatively, compared with middle and apical defects. Although statistically not significant, coronal defects caused lower primary stability values with the tapered design compared with parallel design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This study revealed a highly significant correlation between RFA and EPT scores (Table 4) per group. This observation corroborated the results reported from previous studies [21,22]. The modified drilling protocol for the type B implants recommended an underdimensioned preparation of the implant bed and differed hereby for group B2 from the standard protocol used for group B1 and group A implants.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed a highly significant correlation between RFA and EPT scores (Table 4) per group. This observation corroborated the results reported from previous studies [21,22]. The modified drilling protocol for the type B implants recommended an underdimensioned preparation of the implant bed and differed hereby for group B2 from the standard protocol used for group B1 and group A implants.…”
Section: Discussionsupporting
confidence: 90%
“…Mercan et al created buccal bone defects on coronal, middle, and apical parts of the implants and determined the influence of these defects on ISQ values. 6 They reported that significantly lower ISQ values were noted in the coronal defect group than the other groups and the comparison of middle and apical defect groups showed no significant differences. Akça et al compared RFA values of implants inserted in conventional surgical sockets with circular bone defects at the coronal half and stated that the bone defect group had significantly lower ISQ values than control group with the reduction rate of 38%, from 66.31 to 40.88.…”
Section: Discussionmentioning
confidence: 95%
“…5 The bone quantity around dental implants is mostly affected by cortical bone defects like dehiscence and fenestration because of surgical techniques, the differences of the bone resorption pattern, and anatomical features of the surgical site. 6 Peri-implant dehiscence is defined as the absence of bone initiating from the cervical portion of the implant, while peri-implant fenestration is defined as a buccal or lingual window defect leaving marginal bone at the coronal portion. 7 Immediate implant placement also presents specific challenges for achieving proper primary stability because of the geometric discrepancy between the design of implant and extraction socket.…”
mentioning
confidence: 99%
“…According to the classification of Fleiss, 11 good to excellent results have been reported for the intraobserver and interobserver reliability values of EPT measurements in previously reported ex vivo models. 7,[12][13][14] However, it should be underlined that the EPT measurements from these reported studies were performed only using healing abutments, which had varying heights (3-4 mm).…”
Section: Introductionmentioning
confidence: 99%